Sustainability game. (16th July 2021) - Pedol, Miriam; Biffi, Elena; Melzi, Simone
Abstract: This paper describes a dynamic multistage game in which sustainability is a value that is shared between companies and stakeholders in a competitive market. The game solution could move from a Nash equilibrium to a higher equilibrium, the MES equilibrium, because of the presence of stakeholders who influence the choice and the set of sustainable strategies. Stakeholders provide feedback to companies (by way of awards, ratings, rankings, rebukes, etc.) at every stage of the game. Positive feedback gives a company the chance to expand its business opportunities, leveraging on good reputation, customer loyalty, operational risk mitigation, resilience, employees' cohesion, etc. The interaction between companies and stakeholders also allows companies to seize market opportunities (e.g., supplying sustainable products for responsible customers, sustainable investments for investors, etc.). The sustainability game demonstrates how sustainability can engage the economic system in a market shift.